Lietuvos Respublikos Konstitucinio Teismo doktrinos savininko teisių apsaugos klausimais įvairovės suderinamumas - Taminskas, Algirdas (Vilnius University Open Series, 2024)
This article examines the doctrine of protection of the rights of the owner developed by the Constitutional Court over three decades. This goes back to the origins of the doctrine in the cases of constitutional justice which examined the constitutionality of the legal rules governing restitution relations. The following is a coherent and systematic disclosure of key doctrinal provisions, including those relating to the taking of property for public use and the limitation of the rights of the owner. The above-mentioned analysis of this article is also aimed to determine whether the constitutional justice cases, in which the constitutionality of the provisions of the law providing for limited restitution was decided upon, had any grounds for deciding on the constitutionality of the provisions of the law with respect to the provisions of Article 23(3) of the Constitution.
Keywords: Konstitucinis Teismas; savininko teisių apsauga